Study of psychosocial problems among adolescent students in Pune, India - Shankar Bhosale; Samir A.Singru; Deepak Khismatrao (Al Ameen Medical College, 2015)
Context: Psychosocial health problems are highly prevalent and one of the hidden public health problems amongst the children and adolescents. Early diagnosis by primary care physicians and prompt referral to the specialist is very important for controlling it. Objectives: To screen all school going children for the risk of psychosocial problems, identify risk factors and refer at risk children to the psychiatrist for counseling. Material and Methods: A Cross sectional study in urban and rural field practice area of a teaching hospital in Pune. A screening tool-the youth report of pediatric symptom checklist (Y-PSC) was used .Statistical analysis by Chi square test and Multivariate logistic regression was used as the test for significance. Results: Out of the total 2154 children, 328 (15.2%) were found to be at risk of psychosocial problems. Statistically significant difference was observed as per type of management, medium of education, location of the school, age group, class of the student, total members in the family and socioeconomic status. No significant difference was observed as per gender or the type of the family. However after the application of multinomial logistic regression, significant statistical difference was observed only for the type of management running the schools with significantly more number of proportions of psychological disorders seen in students studying in government run schools. Conclusions: Our study clearly brings out the role of management in psychosocial impairment. The psychosocial impairment is about 15.2% with more impairment seen amongst government schools.